2017
DOI: 10.1103/physrevapplied.8.034003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Control of Metallic Heavy-Metal–Ferromagnet Interfacial States

Abstract: Voltage control effects provide an energy-efficient means of tailoring material properties, especially in highly integrated nanoscale devices. However, only insulating and semiconducting systems can be controlled so far. In metallic systems, there is no electric field due to electron screening effects and thus no such control effect exists. Here we demonstrate that metallic systems can also be controlled electrically through ionic not electronic effects. In a Pt/Co structure, the control of the metallic Pt/Co … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…We investigate the H c of the magnetic Hall crosses by varying the Co thickness (Co t ) and by using electric field control. These results support the mechanism of magneto-ionic effect which has been proposed due to the oxidation at the Co/oxide interface [16,18,19,23,25]. The results also indicate that a thinner polymer accelerates the magneto-ionic effect, leading to further possible optimization for high speed electric field control.…”
Section: Introductionsupporting
confidence: 85%
“…We investigate the H c of the magnetic Hall crosses by varying the Co thickness (Co t ) and by using electric field control. These results support the mechanism of magneto-ionic effect which has been proposed due to the oxidation at the Co/oxide interface [16,18,19,23,25]. The results also indicate that a thinner polymer accelerates the magneto-ionic effect, leading to further possible optimization for high speed electric field control.…”
Section: Introductionsupporting
confidence: 85%
“…Migration of ionic specie that either constitutes the magnetic structure or comes from the external sources can effectively lead to the Prospective Article magnetization modulation in ferromagnetic thin films, which is useful for realizing low power spintronic devices. [69] The construction of foreign magnetic conductive filaments in the insulating matrix also gives rise to TMR and AMR characteristics. Recently it is demonstrated that by accurately controlling the evolution dynamics and thus the dimension of the conductive filaments, NPC with quantized conductance characteristics can be obtained in resistive switching devices.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The PMA of FM/MO bilayers mainly derives from the interfacial FM 3d‐O 2p orbital hybridization that is sensitive to the interfacial oxygen environment . Therefore, extensive works were carried out to tailor the interfacial magnetism by controlling O 2− transport especially using an electric field . The electric field can drive O 2‐ migration to change oxidation state of FM layer, which can regulate the magnetic anisotropy energy (MAE), which paves a feasible way for markedly reducing the switching energy in solid‐state spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extensive works were carried out to tailor the interfacial magnetism by controlling O 2− transport especially using an electric field . The electric field can drive O 2‐ migration to change oxidation state of FM layer, which can regulate the magnetic anisotropy energy (MAE), which paves a feasible way for markedly reducing the switching energy in solid‐state spintronic devices. However, to apply an effective electric field, a thick MO layer of tens of nanometers is required to ensure its good insulativity, which may restrict the application on devices with thin MO layers.…”
Section: Introductionmentioning
confidence: 99%